The Impact of Wi-Fi usage on Students’ Academic Performance - Omar, Mazni; Ahmad, Mazida; Yasin, Azman; Ibrahim, Huda; Ghazali, Osman; Khamis, Shakiroh (International Journal of Engineering and Technology, 2018)
Students’ academic performance is one of the main concerns that demand serious investment from the educational provider. One of the investments pertains to the technology support, namely, the Wi-Fi facility in the campus, aiming at providing students a meaningful learning experience. The study elaborated in this paper, sought explanation on the relationships between the Wi-Fi usage and the students’ academic performance. Using a dataset from 147 Universiti Utara Malaysia (UUM) undergraduate students’ Wi-Fi usage and their academic Cumulative Grade Point Average (CGPA), a Spearman correlation test was executed. The results indicate that Wi-Fi usage does not affect students’ academic performance. Additionally, analyses on Wi-Fi hardcore users also found that the usage does not affect their academic performance. Based on website categories has been used by students, it was found that downloading and online games are the two web categories of usage affecting students’ performance with CGPA between 2.00 to 2.99. Ways to better assist students to use Wi-Fi wisely to benefit their academic performance are also discussed.
Keywords: Wi-Fi; Internet Usage; Student Performance; Academic Performance.